2013
DOI: 10.1097/cmr.0b013e3283625498
|View full text |Cite
|
Sign up to set email alerts
|

Basal caspase-3 activity promotes migration, invasion, and vasculogenic mimicry formation of melanoma cells

Abstract: Melanoma is the least common but most serious form of skin cancer. The leading cause of death in melanoma patients is widespread metastasis caused by increased cell motility and a rich blood supply for tumor cells. A unique form of microcirculation called vasculogenic mimicry, which efficiently supplies blood to tumor cells, has been reported recently. Apoptosis-related protein performs a nonapoptotic function to promote migration and invasion of tumor cells. This study focuses on the nonapoptotic role of casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 22 publications
1
30
0
1
Order By: Relevance
“…Increased caspase 3 expression is found in OSCC compared with normal oral epithelium 76. These findings question the apoptotic role of caspase 3, suggesting its nonapoptotic functions in oral cancers, as implicated in other cancers 77, 78, 79.…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnmentioning
confidence: 87%
“…Increased caspase 3 expression is found in OSCC compared with normal oral epithelium 76. These findings question the apoptotic role of caspase 3, suggesting its nonapoptotic functions in oral cancers, as implicated in other cancers 77, 78, 79.…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnmentioning
confidence: 87%
“…Indeed, survivin and Notch1, involved in M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 melanoma progression, are more expressed in SKMEL28, WM793-B and 1205Lu cells than in less aggressive cell lines. In addition, active caspase-3, which promotes migration and invasion of non apoptotic melanoma cells (Liu et al, 2013), is higher in SKMEL28 and 1205Lu than in the other spheroids. HIF-1α is higher in spheroids derived from advanced stage melanomas (WM266-4 and 1205Lu) ( Figure 1I).…”
Section: Cd271 Inversely Correlates With Melanoma Progression Stage Amentioning
confidence: 99%
“…Thus, it might be counterintuitive that high levels of apoptosis are linked to poor prognosis in cancer (Jalalinadoushan et al, 2004;Leoncini et al, 1993;Nakopoulou et al, 2001;Naresh et al, 2001;Ohbu et al, 1995;Sun et al, 2006). The mechanism behind this unexpected observation is only now beginning to be understood: it has been shown that apoptotic signaling can drive tumor proliferation and invasion in different tumor models (Ballesteros-Arias et al, 2014;Gdynia et al, 2007;Liu et al, 2013;Maeda et al, 2005;Rudrapatna et al, 2013). Likewise, the treatment of tumors by chemotherapy or radiotherapy has recently been shown to induce tumor repopulation by increasing the release of PGE2 by apoptotic cells, which stimulates the growth of surviving tumor cells (Huang et al, 2011;Kurtova et al, 2014).…”
Section: Box 2 Apoptotic Signaling In Tumor Developmentmentioning
confidence: 99%